Sexual orientation and food insecurity: findings from the New York City Community Health Survey. Issue 17 (17th December 2021) - Testa, Alexander; Jackson, Dylan B
Abstract: Objective: Food insecurity is a serious public health concern that disproportionately impacts minority groups. However, limited research has assessed food insecurity among sexual minorities. The current study investigates whether individuals identifying as lesbian/gay or bisexual (LGB) sexual orientation were more likely to experience food insecurity relative to heterosexual persons. Design: Data are from the 2017 and 2018 New York City Community Health Survey. Multinomial logistic regression is used to assess the association between sexual orientation and food insecurity. Setting: A sample of adults (18 years and older) who identify as heterosexual, gay/lesbian or bisexual living in New York City in 2017 and 2018. Participants: 18 610 non-institutionalised adults. Results: Bisexual individuals have significantly higher rates of both mild (relative risk ratio (RRR) = 1·719, 95 % CI 1·148, 2·573) and moderate-to-severe food insecurity (RRR = 1·851, 95 % CI 1·097, 3·122) relative to heterosexual individuals, net of covariates from demographic, household and socio-economic characteristics. Study findings showed no difference in the likelihood of food insecurity between gay/lesbian individuals and heterosexual individuals. Conclusion: Results illustrate a complex interplay between sexual orientation and food insecurity among adults living in New York City. Findings suggest that efforts to connect LGB individuals to public assistance programmes such as Supplemental Nutritional Assistance Program, as well as providing information and connections to food assistance through local LGBTQ+ centres, government agencies (i.e., NYC Human Resources Administration) and non-profit organisations (i.e., Food Bank for New York City) may be beneficial approaches to alleviate food insecurity among this population.